BONE GRAFT SUBSTITUTES WITH BONE CURETTAGE FOR THE TREATMENT OF FIBROUS DYSPLASIA OF RIGHT TIBIA - ALI KHAN, MAZHARUDDIN; MCH; KUMAR, V.R.SUJIT (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Fibrous dysplasia (FD) is benign condition, with an ability to affect any bone in the body and has a wide spectrum of severity. It is a chronic condition of the skeleton where a portion of a bone develops abnormally. We report and discuss a case of six year old male patient suffering from fibrous dysplasia of right tibia, its diagnosis, and management including surgical intervention.Â Bone graft substitute with bone curettage was performed after thorough excision of bone tumour and bone wash. Procedure was carried out under general anaesthesia and c-arm guidance.Â Significant improvement was seen clinically and patient walked eight weeks after surgery, and was able to carry out routine activities normally with a significant improvement in quality of life. This was the latest surgical procedure available for the treatment of FD. Key words: Bone curettage, bone graft substitute with bone curettage, Fibrous dysplasia, quality of life